Omega-3 Fatty Acids and FFAR4 - Oh, Da Young; Walenta, Evelyn (Frontiers in Endocrinology, 2014)
The beneficial roles of omega-3 fatty acids (ω3-FAs) on obesity, type 2 diabetes, and other metabolic diseases are well known. Most of these effects can be explained by their anti-inflammatory effects, triggered through their receptor, G protein-coupled receptor 120 (GPR120) activation. Although the whole mechanism of action is not fully described yet, it has been shown that stimulation of ω3-FA to GPR120 is followed by receptor phosphorylation. This makes GPR120 be capable of interacting to beta-arrestin-2, which in turn results in association, of beta-arrestin-2 to TAB1. This stealing of an important partaker of the inflammatory cascade, leads to interruption of the pathway, resulting in reduced inflammation. Besides this regulation of the anti-inflammatory response, GPR120 signaling also has been shown to regulate glucose homeostasis, adiposity, gastrointestinal peptide secretion, and taste preference. In this review we summarize the current knowledge about the interaction of ω3-FAs with GPR120 and the consequent opportunities for the application of ω3-FAs and possible GPR120 targets.